Equality, freedom and democracy: how important are they for environmental performance? - Toigo, Camila Horst; de Mattos, Ely José (Desenvolvimento e Meio Ambiente, 2021)
The complexity of the relationship between society and the environment is recognized by researchers and practitioners as a major challenge. This article examines how the type of political regime, the degree of political freedom and civil rights, and the level of income concentration relates to environmental performance as measured by the Environmental Performance Index (EPI). The analysis is based on a sample of 161 countries and covers the period 2007-2016, using a fixed effects panel data model. Our findings suggest that democracy as a political regime does not necessarily induce greater commitment to environmental issues. Lower income inequality offers the same results. However, a positive association was found between the expansion of rights and freedoms and the EPI, suggesting that freer countries tend to have better environmental performance. Given the multiplicity of profiles in terms of the nature and depth of democracy and inequality, our study suggest parsimony with more generalist analyses.